Effect of Ionic Liquid Surfactants on Coal Oxidation and Structure - Weiqing Zhang; Shuguang Jiang; Tong Qin; Jianfeng Sun; Chaowei Dong; Qiang Hu (Journal of Analytical Methods in Chemistry)
The effects of six ionic liquids with surfactant property (1-hydroxyethyl-3-methyl imidazolium bis(trifluoromethylsulfonyl)imide ([HOEtMIm][NTf2]), 1-hydroxyethyl-3-methyl imidazolium tetrafluoroborate ([HOEtMIm][BF4]), 1-dodecyl-3- methyl imidazolium bromide ([C12MIm]Br), 1-tetradecyl-3- methyl imidazolium bromide ([C14MIm]Br), trioctyl methyl ammonium chloride ([N8,8,8,1])Cl, and tetraethyl ammonium chloride ([N2,2,2,2]Cl)) on the oxidation characteristics and functional groups of coal were studied by means of critical micelle concentration, surface tension, thermogravimetric analysis, temperature-programmed oxidation, and Fourier transform infrared spectroscopy (FTIR) measurements. The lower critical micelle concentration for the ionic liquids except the [N2,2,2,2]Cl suggests the favorable surface activity of these ionic liquids. The surface activities of [N8,8,8,1]Cl, [C14MIm]Br, [C12MIm]Br, and [HOEtMIm][NTf2] were high, while that of [N2,2,2,2]Cl was relatively lower. The thermal stabilities of [HOEtMIm][NTf2] and [HOEtMIm][BF4] were high, while those of [N8,8,8,1]Cl and [N2,2,2,2]Cl were lower. The oxidation activities of ionic liquid-mixed coals were weakened to different degrees except [N8,8,8,1]Cl-mixed coal, because of the poor thermal stability and decomposition of [N8,8,8,1]Cl accelerating the coal oxidation. The other five ionic liquids were suitable for inhibiting coal oxidation, particularly the [HOEtMIm][BF4] and [HOEtMIm][NTf2] with higher inhibition rate, longer inhibition time, and also better thermal stabilities. The activation energy results further confirmed such inhibition effect. The functional group results showed that treatment of ionic liquids on coal can change the contents of hydrogen bonds, aliphatic groups, and aromatic groups in coal. It was inferred that the [HOEtMIm][BF4], [HOEtMIm][NTf2], and [C14MIm]Br were more effectively to affect coal structure and decrease coal oxidation activity.